Development of an experimental ovarian tumor: immunocytochemical analysis - Sorianello, Eleonora Mariana (2002)
The aim of the present work was to study whether immunocytochemical parameters present in the normal ovary were altered after tumor development under high gonadotropin levels. These results indicated that luteoma most likely develop from unruptured follicles by hypertrophy and proliferation of follicular cells. Circulating gonadotropins seem to play a fundamental role in maintaining the expression of proteins typically expressed in normal ovary, while avoiding apoptosis in this tissue.